GRAMMAR ERROR BY STUDENTS IN TRANSLATING INDONESIAN INTO ENGLISH - Maniar, Diani Syahputri , Wiki Tedi Rahmawati (EXCELLENCE: Journal of English and English Education, 2021)
This research was to analyze the students’ grammar errors on the use of present tense and past tense in translating Indonesian sentence into English. The aims were to find out what errors were made by the students and what error was the dominant one. The method used was descriptive qualitative. It was conducted at SMP Swasta Dwitunggal Tanjung Morawa in academic year 2018 – 2019. The population was the students of the eighth grade consisted of 3 classes with the total number of population was 138. The sample was the class VIII-3 consisted of 41 students which was obtained through cluster random sampling with lottery technique. The instrument used was a translation test which consisted of 20 items of Indonesian sentence. Through the data analysis, it was obtained that there were four types of errors made by the eighth grade students, namely error of omission (17.22%), error of addition (32.05%), error of miss-formation (34.44%), and error of miss-ordering (12.91%). The most dominant error was error of miss-formation.